Application of Beeswax Emulsion Edible Coating with the Addition of Sesame Oil and Lemongrass Oil to Extend the Shelf Life of Tomatoes (Solanum lycopersicum Mill.) - khodijah, Nyayu Siti; Isam, Zurfa; Kusmiadi, Riwan (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
The use of edible coating is a way to increase the shelf life of horticultural products. This study aims to determine the effect of the application of beeswax emulsion coating concentration with the addition of sesame oil and lemongrass oil as an edible coating to extend the shelf life of tomatoes. This research was conducted in January ̶ March 2020. The experimental design used was a Randomized Block Design (RBD) with various concentrations of beeswax emulsion combination of 0,5% lemongrass oil and 0,5% sesame oil with various concentrations of beeswax (0%, 1%, 2%, 3%). Beeswax edible coating solution is applied to the tomatoes by dipping the tomatoes into the solution. The results showed that the application of beeswax emulsion edible coating with the addition of sesame oil and citronella oil to tomatoes with a concentration of 3% was able to maintain the fruit's shelf life for 12 days of storage and gave good results on weight loss, total dissolved solids and total acid variables in tomatoes compared to other treatments.